Working with psychotic anxieties in the group. (September 2020) - Noack, Amélie
The training of group analysts teaches the conductor mainly how to work with neurotic symptoms and anxieties. This article attempts to widen this frame by considering how to work with psychotic anxieties stemming from experiences in early infancy when the environment failed the patient in providing secure holding and a facilitating environment for growth. Using insights by Jung based on his association experiments and his complex theory, as well as Winnicott's view of psychotic illness as a defence and his understanding of working with primitive agonies, this article describes how to work with psychotic anxieties in the group.